The level index of flexibility of the basketball players in the age of 10–12 years - Кравцова, О. О. (Slobozhanskyi Herald of Science and Sport, 2011)
The article is devoted to the level index of flexibility of the basketball players. It was defined according to the standard methodic. The basketball players of the present age have sufficient level of development flexibility of the spinal column, and insufficient activity in the hip joint and shoulder joint.